(untitled) (Revista Espinhaço, 2021)
Employment creation, especially among the youth, remains a global issue. is study examines youth participation and labor demand in agriculture using the 2015/16 Living Standard Measurement Survey-Integrated Survey Agriculture (LSMS-ISA) data. e analytical tools employed in the study include descriptive statistics, Logistic and Tobit regression models. Summary statistics showed that males participate more than females in Nigerian agriculture. e farmers were smallholders. e results revealed low participation of youth in Nigerian agriculture. Farm size, access to credit and household size significantly influenced youth participation in Nigerian agriculture. Age, use of inorganic fertilizer, farm income, household size and cultivated farm size were labor enhancing. e study suggests that efforts to shape future work in Nigerian agriculture especially among youth should include among other things, access to land and provision of credit facilities.